Breathe Better: The Role of Pursed Lips Breathing Therapy in Chronic Bronchitis Patients - Pangestu, Adinda Widia; Sutawardana, Jon Hafan; Murtaqib; Mustakim (Al-Hijrah Indonesia, 2025)
Chronic bronchitis is an inflammatory disease of the bronchial respiratory tract that lasts more than 3 months or several times in 2 years. Symptoms in patients with chronic bronchitis can affect breathing patterns, including dyspnea, respiratory frequency, depth of breathing, and oxygen saturation. Providing Pursed Lip Breathing therapy can create resistance to the air coming out of the lungs and open the airways to improve breathing patterns. This study aimed to analyze the effectiveness of Pursed Lip Breathing therapy on breathing patterns in patients with chronic bronchitis. This descriptive, experimental research was conducted on a Chronic Bronchitis patient. Patient in the Inpatient Room of a government hospital. The implementation of Pursed Lip Breathing therapy was carried out for 4 days, where each day, there was one session of 8-10 repetitions of abdominal breathing followed by Pursed Lip Breathing therapy for 8 minutes. Data analysis was explained descriptively daily to compare the improvement in breathing patterns between pre and post-therapy values. The study results showed significant improvement in breathing patterns, including the level of dyspnea, depth of breathing, orthopnea, use of accessory muscles for breathing, and vital signs, including RR, SPO2, and the patient's blood pressure. This study concluded that Pursed Lip Breathing therapy effectively improved breathing patterns in Chronic Bronchitis patients. The results of this study indicate that pursed lip breathing therapy is safe to apply to patients undergoing treatment. Nurses can apply pursed lip breathing therapy and implement siki for patients with breathing pattern disorders.